AS REPRESENTAÇÕES SOCIAIS SOBRE A VIOLÊNCIA NOS JORNAIS ONLINE ENVOLVENDO ADOLESCENTES EM PONTA GROSSA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
When words, images and ideas are related and then shared by subjects, they create a reality. It is the context of communication that social representations take shape as elements which are present in social relations, thereby constituting a social reality. On such presupposition, this thesis aims at gaining an understanding of how the local online newspapers Diário dos Campos and Jornal da Manhã, in the city of Ponta Grossa, Paraná (Brazil), addressed issues related to “violence” committed by male teenagers in conflict with the law throughout the year of 2011. The Theory of Social Representations (TSR) was adopted as a theoretical framework, in order to reconstruct the object of research, namely, the social representations of online newspapers. From a methodological point of view, qualitative research was the starting point, and the data were then tabulated following a quantitative research. A total of 65 online newspaper reports on violence committed in 2011 by male teenagers in conflict with the law were catalogued. The analysis of the data was developed in accordance with the research procedure of content analysis, taking into account the frequency of the data in the aforementioned newspapers, and, hence, setting up categories, which were then addressed in light of the Theory of Social Representations (TSR). In its conclusion, the thesis attests that, generally, the social representations in the online newspapers with the law limit the discussion to police issues, thereby discontextualizing the events. Besides, violence is associated with infractional acts, so that violence and crime are seen as synonymous, and this creates a stereotype for these teenagers. Also, social representations have the same way to approach and discuss violence, with little divergence between then.
Keywords: representações sociais; violência; adolescentes em conflito com a lei; jornais online; violence; teenagers in conflict with the law; online newspapers; social representations; CNPQ::CIENCIAS SOCIAIS APLICADAS